Elective surgery patients walk to operating room instead of wheeled in on trolley: patient centered care (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Habits and beliefs of earlier practitioners influence medicine. We continue to wheel in the elective surgery patients to operating room (OR) which makes them feel not in self-control and increases anxiety. With few exceptions of heavily sedated, in severe pain or frail patients, most prefer to walk to the OR accompanied by nurse and family, if given the opportunity, in line with patient centered care. We aim to assess feasibility to allow elective surgery patients walk to OR accompanied by nurse and family member.Methods: This was a cross-sectional observation of 100 consecutive elective surgery patients admitted at surgery department, Patan Hospital, Nepal. Adult patients of 15 years or above were allowed to walk to OR accompanied by a nurse and family members. Demographic profile, patient satisfaction, anxiety on arriving to OR, patient feeling of autonomy were recorded to assess patient centered care. Microsoft Excel was used to descriptively analyze the data. Ethical approval was obtained.Results: Of 100 consecutive patients, 62 were female and 38 male, average age 52 years (range 15 to 72), and abdomen surgery 62 (62%). Two patients did not want to walk. The 98 patients who walked to the OR, all were satisfied and 89 were not anxious.Conclusions: Elective surgery patients (98 out of 100) accompanied by nurse and family members walked to operating room satisfied and were not anxious.